Evaluation of Corruption Eradication and Strengthening of Corruption Eradication Prevention in Medan City - Nur Jannah Al Baiti; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Corruption is systematically defined as an extraordinary crime that requires extraordinary efforts to eradicate it. Therefore, from the beginning, KPK was given extraordinary power (superbody) to uncover malicious plots and attack the strongest corrupt bases. KPK has gradually regained public confidence, as evidenced by the use of state-of-the-art investigative methods such as strong wiretapping, fraudulent investigations, surveillance and forensic audits. The provisions of Articles 6b and 8 of Law No. 19 of 2019, which amends Law No. 30 of 2002, include the Anti-Corruption Commission and the Anti-Corruption Commission (KPK). The Monitoring and Prevention Center (MCP) was established by KPK in collaboration with the Ministry of Interior and BPKP to streamline anti-corruption coordination in Medan.